2010
DOI: 10.1111/j.1467-8535.2010.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the factors that affect individuals’ utilisation of online learning systems: An empirical study combining the task technology fit model with the theory of planned behaviour

Abstract: Understanding learners' behaviour, perceptions and influence in terms of learner performance is crucial to predict the use of electronic learning systems. By integrating the task-technology fit (TTF) model and the theory of planned behaviour (TPB), this paper investigates the online learning utilisation of Taiwanese students. This paper provides a better understanding of individual, technological and social factors regarding online learning system performance. A total of 870 students who were earlier introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 40 publications
(116 reference statements)
3
52
1
Order By: Relevance
“…An early study that applied attitude, subjective norms, and perceived behavioral control to predict ICT adoption intention found that all three variables were significant predictors of college students' intention to utilize a shop-bot to purchase books online (Gentry & Calantone, 2002). Additional research reported that these three independent variables significantly contributed to the formation of behavioral intentions for utilizing an online learning system (Yu & Yu, 2010).…”
Section: Theory Of Planned Behaviormentioning
confidence: 97%
“…An early study that applied attitude, subjective norms, and perceived behavioral control to predict ICT adoption intention found that all three variables were significant predictors of college students' intention to utilize a shop-bot to purchase books online (Gentry & Calantone, 2002). Additional research reported that these three independent variables significantly contributed to the formation of behavioral intentions for utilizing an online learning system (Yu & Yu, 2010).…”
Section: Theory Of Planned Behaviormentioning
confidence: 97%
“…Park et al, 2012;Shin, 2009;Wang & Wang, 2010). There is previous literature illuminating the effects of online or virtual learning systems on students' learning outcome as well as engagement and satisfaction (Chen et al, 2010;Chou & Liu, 2005;Davis & Graff, 2005;Yu & Yu, 2010); however, there is very limited literature examining the effect of smartphone use on students' learning outcome or engagement. The mediator between technology self-efficacy and behavioural intention was indicated as perceived ease of use and perceived usefulness of a new technology (Gu et al, 2009;S.…”
Section: Indirect Effectmentioning
confidence: 99%
“…The technologies in such cases were diverse types of digital devices or online systems including e-books, learning management systems, smartphones, and others (e.g., digital video tools; Davies & Graff, 2005;Lin & Wang, 2012;Shin, Shin, Choo, & Beom, 2011;Yi et al, 2016). Many studies that examined the effects of online or virtual learning systems illuminated their significant impacts on learning outcomes as well as student engagement or satisfaction, particularly in comparison with traditional learning systems (Chen, Lambert, & Guidry, 2010;Chou & Liu, 2005;Davies & Graff, 2005;Yu & Yu, 2010).…”
Section: Technologies Efficacy Behavioural Intention and Academicmentioning
confidence: 99%
“…The task–technology fit theory directly affects electronic learning system utilization and indirectly affects electronic learning systems (Yu and Yu, ). As an extrinsic motivational factor, the task–technology fit is associated positively not only with perceived ease of use but also with the perceived usefulness of hotel information systems (Kim et al ., ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%